2013
DOI: 10.1177/0021998313515019
|View full text |Cite
|
Sign up to set email alerts
|

Advanced accelerated testing methodology for long-term life prediction of CFRP laminates

Abstract: An advanced accelerated testing methodology (ATM-2) for long-term life prediction of CFRP laminates exposed to actual loading with a general stress and temperature history is proposed based on the conventional accelerated testing methodology (ATM-1) established for the long-term life prediction of CFRP laminates exposed to stress and temperature. The most important condition for ATM-1 is that the time-temperature superposition principle held for the viscoelastic behavior of matrix resin holds also for the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…15 In our previous papers, the statistical formulation of static, creep, and fatigue strengths of CFRP has been proposed based on the matrix resin viscoelasticity. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…15 In our previous papers, the statistical formulation of static, creep, and fatigue strengths of CFRP has been proposed based on the matrix resin viscoelasticity. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that fatigue models by Miyano et al [9,10,11] and Reifsnider et al [12] are meant to account for viscoelastic effects while the model by Epaarachchi and Clausen [13] includes the effect of frequency under the assumption of negligible hysteretic heating. However, Guedes [24] has suggested that the linear cumulative law employed by Myiano may not fare well for complex fatigue loads or long lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of ATM was confirmed for CFRP laminates and structures combined with PAN-based carbon fibers and thermosetting resins (Miyano et al 1999a(Miyano et al , b, 2008. Furthermore, advanced ATM (Nakada and Miyano 2015) was proposed by which the formulation for the master curves of time-temperature-dependent fatigue strength was done based on a theory reported by Christensen and Miyano (2006), which describes the crack kinetics in viscoelastic body statistically.…”
Section: Introductionmentioning
confidence: 99%